Super durable exterior wall coating and preparation method thereof

By using modified filler slurry and other additives in exterior wall coatings, the problem of insufficient durability of existing coatings is solved, and higher high temperature, weather, water and adhesion properties are achieved.

CN119264742BActive Publication Date: 2025-02-25Jiangsu Jiunuo Architectural Materials Technology Co Ltd
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411797334.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-25
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

Existing exterior wall coatings are insufficient in complex environments such as long-term exposure to sunlight, rainwater, low temperatures and sun exposure, especially in terms of poor performance in terms of oxidation resistance, adhesion and fluidity.

Method used

Adopt a formula of ultra-durable exterior wall coating, including fluorocarbon emulsion, modified filler slurry with solid content of 20% to 30%, film forming agent, pH adjuster, ordinary filler, dispersant, leveling agent, and increase Thickeners and antioxidants change the crystal form of titanium dioxide through fine grinding and increase defects in the SiO2 lattice, forming composite particles to improve adhesion and anti-aging ability.

Benefits of technology

It significantly improves the high temperature resistance, weather resistance, water resistance, adhesion and friction resistance of the paint, enhances the anti-oxidation and ultraviolet resistance, and extends the service life of the paint.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a super durable exterior wall coating and a preparation method thereof, which comprises, by weight, 20 to 30 parts of fluorocarbon emulsion, 20 to 25 parts of modified filler slurry with a solid content of 20% to 30%, 2 to 3 parts of film former, 2 to 3 parts of pH adjuster, 20 to 40 parts of common filler, 0.3 to 0.9 parts of dispersant, 1.0 to 1.6 parts of leveling agent, 0.1 to 0.5 parts of thickener, and 0.1 to 0.2 parts of antioxidant. The present invention belongs to the technical field of coatings, and the purpose of the present invention is to solve the problem of low durability of coatings in the prior art. The technical effect achieved is: having excellent durability, including excellent high temperature resistance, weather resistance, water resistance, good adhesion, friction resistance, strong anti-oxidation and anti-ultraviolet ability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coatings, and in particular to a super-durable exterior wall coating and a preparation method thereof. Background Art

[0002] During the use of exterior wall paint, it is exposed to complex environmental factors such as direct sunlight, rain, low temperature, and exposure to the sun for a long time, and its internal structure will age spontaneously. Microparticle fillers are one of the main components of paint. In water-based paints, they often increase the wear resistance of the paint, but they do not have a good effect on the paint's antioxidant properties, adhesion, fluidity, etc., and often have the opposite effect due to excessive proportions, resulting in reduced paint durability.

[0003] In the prior art, CN 115558397 A proposes a highly durable exterior wall paint and a preparation method thereof, comprising the following raw materials in parts by weight: 80-100 parts of modified resin, 8-10 parts of antifouling particles, 5-10 parts of photoinitiator, 20-30 parts of emulsifier, and 150-200 parts of water. This solution is mainly to improve the hydrophobic effect and enhance the water resistance of the exterior wall paint, but does not mention enhancing antioxidant properties, adhesion, and other aspects.

[0004] CN 104804577 A proposes a durable exterior wall paint, which has good durability by adding slag micropowder, antimony tin oxide, round-grained quartz sand, etc., which essentially enhances the rigidity and wear resistance of the paint, and does not involve considerations of the paint's oxidation resistance, adhesion, fluidity, etc. Summary of the invention

[0005] To solve the above problems, the present invention provides a super durable exterior wall coating and a preparation method thereof, which has excellent high temperature resistance, weather resistance, water resistance, adhesion and friction resistance.

[0006] To achieve the above object, the technical solution of the present invention is:

[0007] A super durable exterior wall paint, comprising, by weight:

[0008] 20~30 parts of fluorocarbon emulsion,

[0009] 20~25 parts of modified filler slurry with a solid content of 20%~30%,

[0010] Film-forming agent is 2~3 parts,

[0011] pH adjuster 2~3 parts,

[0012] Ordinary fillers are 20~40 parts,

[0013] Dispersant is 0.3~0.9 parts,

[0014] Leveling agent is 1.0~1.6 parts,

[0015] Thickener is 0.1~0.5 parts,

[0016] The amount of antioxidant is 0.1~0.2 parts.

[0017] Preferably, the modified filler slurry is prepared by the following method:

[0018] (1) Prepare a soluble silicate solution A with a mass fraction of 8-15%;

[0019] (2) Take 10-20 parts of solution A, 4-10 parts of titanium dioxide with a mesh size of more than 400, 0.1-0.3 parts of La2O3, 3-5 parts of Al2O3 with a mesh size of more than 400, 20-40 parts of SiO2 powder with a mesh size of more than 2000, 0.4-1 parts of water-soluble silicone oil, and 0.1-0.3 parts of dispersant, add them to a sand mill or a ball mill, and grind them into a slurry particle size of more than 2000 mesh to obtain slurry B;

[0020] (3) Prepare Ca2+ with pH of 4.5-6.5 x (H) 6-2x (C6H5O7)2 solution C, slurry B is mixed with solution C in a ratio of 1:1-1:3, stirred evenly, and then concentrated at 50-70°C to a modified filler slurry with a solid content of 20%~30%, 0.5<x<2.5.

[0021] The solute of the soluble silicate solution A is sodium silicate or potassium silicate, and the modulus is 2-5, which can improve the weathering resistance of the exterior wall coating. In addition to reducing the particle size of the powder, the mechanical energy of the fine grinding process can also change the crystal form of titanium dioxide to rutile type, and can also increase the defects in the SiO2 lattice. At the same time, the fine grinding process produces more crystal boundaries, which can increase the specific surface area and surface activity of the powder, so that the powder has stronger adhesion.

[0022] As a fine grinding medium, the silicate ions in the soluble silicate solution A can be adsorbed onto the newly formed grain boundaries of titanium dioxide, Al2O3 and other powders during the fine grinding process. In the subsequent step (3) of mixing slurry B with solution C, these silicate ions on the grain boundaries will capture H + , converted into SiO2. In this process, La2O3 in slurry B has reacted into La(OH)3 or La2(CO3)3 during the refinement process. Part of Ca in solution C in step (3) x (H) 6-2x (C6H5O7)2 (where 1≤x≤3) C6H5O7 3-It can react with La(OH)3 and La2(CO3)3 to generate LaC6H5O7, and form a co-precipitation with SiO2 generated on the surface of the powder grain boundary; the silicate ions not attached to the new grain boundary are partially converted into silica sol during the concentration process.

[0023] In the modified filler slurry of the present invention, the components of the modified filler slurry are not simply mixed. The coprecipitation reaction of several substances on the new grain boundaries of titanium dioxide, Al2O3, etc. can form a complex particle structure, which can make the contact interface energy band present diversified characteristics, thereby enhancing the adhesion, anti-aging ability and wear resistance of the coating on a macro scale, and ultimately improving the durability of the coating. The traditional technical means are only mechanical mixing, which is slightly inferior to the present invention in terms of particle distribution uniformity and comprehensive functional effects.

[0024] Select Ca x (H) 6-2x (C6H5O7)2 is used as the solvent of solution C because of its low solubility. Low solubility means that excessive citrate will not be introduced, the process is highly controlled, and there is a larger buffer space. Experiments have found that the selection of high-solubility citrate introduces too much C6H5O7 3- This will lead to poor stability and reduced durability of the subsequent coating. x (H) 6-2x (C6H5O7)2 solution can control the above coprecipitation reaction by adjusting the pH, and a small amount of C6H5O7 added to the coating 3- It can enhance the stability of the coating, making it difficult to delaminate and deteriorate during storage and use. It can increase the gloss and transparency of the coating when used in combination with other additives, making the coating easier to process and apply, and improving the efficiency and quality of coating. In addition to the above effects, the SiO2 / LaC6H5O7 co-precipitation mentioned in the present invention can act as a preservative in the coating when compounded with the new grain boundary of titanium dioxide. The SiO2, LaC6H5O7 and titanium dioxide composite particles change the original band structure of titanium dioxide, making it have strong anti-ultraviolet and anti-oxidation capabilities; when compounded with the new grain boundary of Al2O3, it can enhance the strength of the coating after curing, and at the same time enhance the binding force with fluorocarbon, play a pinning role on the coating base material (fluorocarbon), prevent excessive displacement of the polymer chain, and improve the strength of the coating.

[0025] The water-soluble silicone oil in step (2) of the present invention is a polysiloxane-polyalkoxy ether copolymer, which also has the effect of acting as a leveling agent. In step (3) of the present invention, the water content is controlled by thermal evaporation. During this process, the soluble silicone oil is always present in the slurry and can be coated on the surface of the slurry particles to enhance fluidity. A low solid content of the modified filler slurry of the present invention will lead to a high water content in the subsequent coating, which is not easy to form and solidify; a high solid content will lead to poor fluidity.

[0026] In the ultra-durable exterior wall paint of the present invention, the silicate ions not attached to the new grain boundaries in step (3) are converted into silica sol which is dispersed at the oil-water interface and becomes a connecting bridge between the fluorocarbon emulsion and the water-soluble silicone oil, thereby enhancing the fluidity of the paint and improving its weather resistance and anti-fouling and water-resistant properties.

[0027] Preferably, in step (3), the slurry B and solution C are mixed and stirred in a ratio of 1:1-1:3, and then concentrated at 50-70°C to a modified filler slurry with a solid content of 20%-30%. Too high a temperature can cause problems such as sticking to the pan, carbonization, and agglomeration.

[0028] Preferably, the film-forming agent is alcohol lipid twelve. Experiments have shown that it can also be other high-carbon alcohols or ester solvents.

[0029] Preferably, the common filler includes at least three of limestone, diatom mud, mica powder and talcum powder, and the particle size of the common filler is greater than 1500 mesh.

[0030] Preferably, the dispersant is sodium lignin sulfonate or sodium humate.

[0031] Preferably, the leveling agent is carboxymethyl cellulose; the thickener is hydroxyethyl cellulose; and the antioxidant is BHT antioxidant.

[0032] The present invention also proposes a method for preparing the above-mentioned ultra-durable exterior wall coating, and the preparation steps are as follows:

[0033] (a) preparing a modified filler slurry;

[0034] (b) Add the modified filler slurry into the stirrer according to the formula ratio, add the thickener, pH adjuster, dispersant, leveling agent, and antioxidant, and stir at 2000-3000 r / min for 20-30 minutes; then slowly add the ordinary filler, increase the stirring speed to 3500-4500 r / min, and stir for 20-30 minutes;

[0035] (c) Finally, add fluorocarbon emulsion, then stir at 500-1000 r / min for 5-15 min and let stand, and vacuum and defoam to obtain ultra-durable exterior wall coating.

[0036] Compared with the prior art, the present invention achieves the following beneficial effects:

[0037] 1. Complex physical and chemical reactions occurred during the preparation of modified filler slurry, causing lanthanum salts and SiO2 to coprecipitate on the new grain boundaries of titanium dioxide, Al2O3 and other particles in the slurry, forming composite particles, changing the energy band structure of the contact interface of different components, so that the modified filler can improve the adhesion, anti-oxidation, anti-ultraviolet, and wear resistance of the coating. At the same time, since the modified filler participates in the preparation of the coating in the form of slurry, it has a better dispersion effect and improves the uniformity of the coating performance;

[0038] 2. The ultra-durable exterior wall coating proposed by the present invention has extremely good durability, excellent high temperature resistance, weather resistance, water resistance, good adhesion ability, friction resistance, and strong antioxidant and UV resistance. DETAILED DESCRIPTION

[0039] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Example 1

[0041] A super durable exterior wall paint, comprising, by weight:

[0042] 20 parts of fluorocarbon emulsion,

[0043] 25 parts of modified filler slurry with a solid content of 20%,

[0044] The film-forming agent is 12 parts of alcohol fat,

[0045] 2 parts of pH adjuster,

[0046] The common filler is 20 parts (5 parts limestone, 5 parts diatom mud, 5 parts mica powder and 5 parts talcum powder, the particle size of the common filler is 2000 mesh) and the dispersant is sodium lignin sulfonate, 0.3 parts,

[0047] The leveling agent is 1.0 part of carboxymethyl cellulose,

[0048] The thickener is 0.1 part of hydroxyethyl cellulose,

[0049] The antioxidant is 0.1 part of BHT antioxidant;

[0050] The preparation method is:

[0051] (a) Preparation of modified filler slurry: (1) Prepare a soluble silicate solution A with a mass fraction of 10%; (2) Take 20 parts of solution A, 5 parts of 400-mesh titanium dioxide, 0.2 parts of La2O3, 4 parts of 400-mesh Al2O3, 3 parts of 2000-mesh SiO2 powder, 0.5 parts of water-soluble silicone oil, and 0.1 parts of dispersant, add them to a sand mill or a ball mill, and grind them to a slurry particle size of >2000 mesh to obtain slurry B; (3) Prepare a CaH4(C6H5O7)2 solution C with a pH of 4.5, mix slurry B with solution C in a ratio of 1:1, stir evenly, and then concentrate at 50°C to a modified filler slurry with a solid content of 20%;

[0052] (b) Add the modified filler slurry into the stirrer according to the proportion, add the thickener, dispersant, leveling agent and antioxidant, and stir at 2000r / min for 25min; then slowly add the ordinary filler, increase the stirring speed to 3500r / min, and stir for 25min;

[0053] (c) Finally, fluorocarbon emulsion was added, and then stirred at 1000 r / min for 10 min and allowed to stand, and vacuumed and defoamed to obtain an ultra-durable exterior wall coating.

[0054] Example 2

[0055] The difference from Example 1 is that 20 parts of modified filler slurry with a solid content of 20% are added, specifically, a super durable exterior wall coating, which includes, by weight:

[0056] 20 parts of fluorocarbon emulsion,

[0057] 20 parts of modified filler slurry with a solid content of 20%,

[0058] The film-forming agent is 12 parts of alcohol fat,

[0059] 2 parts of pH adjuster,

[0060] The common filler is 20 parts (5 parts limestone, 5 parts diatom mud, 5 parts mica powder and 5 parts talcum powder, the particle size of the common filler is 2000 mesh) and the dispersant is sodium lignin sulfonate, 0.3 parts,

[0061] The leveling agent is 1.0 part of carboxymethyl cellulose,

[0062] The thickener is 0.1 part of hydroxyethyl cellulose,

[0063] The antioxidant is 0.1 part of BHT antioxidant;

[0064] The preparation method is:

[0065] (a) Preparation of modified filler slurry: (1) Prepare a soluble silicate solution A with a mass fraction of 10%; (2) Take 20 parts of solution A, 5 parts of 400-mesh titanium dioxide, 0.2 parts of La2O3, 4 parts of 400-mesh Al2O3, 3 parts of 2000-mesh SiO2 powder, 0.5 parts of water-soluble silicone oil, and 0.1 parts of dispersant, add them to a sand mill or a ball mill, and grind them to a slurry particle size of >2000 mesh to obtain slurry B; (3) Prepare a CaH4(C6H5O7)2 solution C with a pH of 4.5, mix slurry B with solution C in a ratio of 1:1, stir evenly, and then concentrate at 50°C to a modified filler slurry with a solid content of 20%;

[0066] (b) Add the modified filler slurry into the stirrer according to the proportion, add the thickener, pH adjuster, dispersant, leveling agent and antioxidant, and stir at 2000r / min for 25min; then slowly add the ordinary filler, increase the stirring speed to 3500r / min, and stir for 25min;

[0067] (c) Finally, fluorocarbon emulsion was added, and then stirred at 1000 r / min for 10 min and allowed to stand, and vacuumed and defoamed to obtain an ultra-durable exterior wall coating.

[0068] Example 3

[0069] The difference from Example 1 is that the solid content of the modified filler slurry is 25%, specifically, a super durable exterior wall coating, comprising, by weight:

[0070] 20 parts of fluorocarbon emulsion,

[0071] 25 parts of modified filler slurry with a solid content of 25%,

[0072] The film-forming agent is 12 parts of alcohol fat,

[0073] 2 parts of pH adjuster,

[0074] The common filler is 20 parts (5 parts limestone, 5 parts diatom mud, 5 parts mica powder and 5 parts talcum powder, the particle size of the common filler is 2000 mesh) and the dispersant is sodium lignin sulfonate, 0.3 parts,

[0075] The leveling agent is 1.0 part of carboxymethyl cellulose,

[0076] The thickener is 0.1 part of hydroxyethyl cellulose,

[0077] The antioxidant is 0.1 part of BHT antioxidant;

[0078] The preparation method is:

[0079] (a) Preparation of modified filler slurry: (1) Prepare a soluble silicate solution A with a mass fraction of 10%; (2) Take 20 parts of solution A, 5 parts of 400-mesh titanium dioxide, 0.2 parts of La2O3, 4 parts of 400-mesh Al2O3, 3 parts of 2000-mesh SiO2 powder, 0.5 parts of water-soluble silicone oil, and 0.1 parts of dispersant, add them to a sand mill or a ball mill, and grind them to a slurry particle size of >2000 mesh to obtain slurry B; (3) Prepare a CaH4(C6H5O7)2 solution C with a pH of 4.5, mix slurry B with solution C in a ratio of 1:1, stir evenly, and then concentrate at 50°C to a modified filler slurry with a solid content of 25%;

[0080] (b) Add the modified filler slurry into the stirrer according to the proportion, add the thickener, pH adjuster, dispersant, leveling agent and antioxidant, and stir at 2000r / min for 25min; then slowly add the ordinary filler, increase the stirring speed to 3500r / min, and stir for 25min;

[0081] (c) Finally, fluorocarbon emulsion was added, and then stirred at 1000 r / min for 10 min and allowed to stand, and vacuumed and defoamed to obtain an ultra-durable exterior wall coating.

[0082] Example 4

[0083] The difference from Example 1 is that the solid content of the modified filler slurry is 30%, specifically, a super durable exterior wall coating, comprising, by weight:

[0084] 20 parts of fluorocarbon emulsion,

[0085] 25 parts of modified filler slurry with a solid content of 30%,

[0086] The film-forming agent is 12 parts of alcohol fat,

[0087] 2 parts of pH adjuster,

[0088] The common filler is 20 parts (5 parts limestone, 5 parts diatom mud, 5 parts mica powder and 5 parts talcum powder, the particle size of the common filler is 2000 mesh) and the dispersant is sodium lignin sulfonate, 0.3 parts,

[0089] The leveling agent is 1.0 part of carboxymethyl cellulose,

[0090] The thickener is 0.1 part of hydroxyethyl cellulose,

[0091] The antioxidant is 0.1 part of BHT antioxidant;

[0092] The preparation method is:

[0093] (a) Preparation of modified filler slurry: (1) Prepare a soluble silicate solution A with a mass fraction of 10%; (2) Take 20 parts of solution A, 5 parts of 400-mesh titanium dioxide, 0.2 parts of La2O3, 4 parts of 400-mesh Al2O3, 3 parts of 2000-mesh SiO2 powder, 0.5 parts of water-soluble silicone oil, and 0.1 parts of dispersant, add them to a sand mill or a ball mill, and grind them to a slurry particle size of >2000 mesh to obtain slurry B; (3) Prepare a CaH4(C6H5O7)2 solution C with a pH of 4.5, mix slurry B with solution C in a ratio of 1:1, stir evenly, and then concentrate at 50°C to a modified filler slurry with a solid content of 30%;

[0094] (b) Add the modified filler slurry into the stirrer according to the proportion, add the thickener, pH adjuster, dispersant, leveling agent and antioxidant, and stir at 2000r / min for 25min; then slowly add the ordinary filler, increase the stirring speed to 3500r / min, and stir for 25min;

[0095] (c) Finally, fluorocarbon emulsion was added, and then stirred at 1000 r / min for 10 min and allowed to stand, and vacuumed and defoamed to obtain an ultra-durable exterior wall coating.

[0096] Example 5

[0097] The difference from Example 1 is that in step (3) of preparing the modified filler slurry, the slurry B is mixed with the solution C in a ratio of 1:2 and stirred evenly. Specifically, a super durable exterior wall coating comprises, in parts by weight:

[0098] 20 parts of fluorocarbon emulsion,

[0099] 25 parts of modified filler slurry with a solid content of 20%,

[0100] The film-forming agent is 12 parts of alcohol fat,

[0101] 2 parts of pH adjuster,

[0102] The common filler is 20 parts (5 parts limestone, 5 parts diatom mud, 5 parts mica powder and 5 parts talcum powder, the particle size of the common filler is 2000 mesh) and the dispersant is sodium lignin sulfonate, 0.3 parts,

[0103] The leveling agent is 1.0 part of carboxymethyl cellulose,

[0104] The thickener is 0.1 part of hydroxyethyl cellulose,

[0105] The antioxidant is 0.1 part of BHT antioxidant;

[0106] The preparation method is:

[0107] (a) Preparation of modified filler slurry: (1) Prepare a soluble silicate solution A with a mass fraction of 10%; (2) Take 20 parts of solution A, 5 parts of 400-mesh titanium dioxide, 0.2 parts of La2O3, 4 parts of 400-mesh Al2O3, 3 parts of 2000-mesh SiO2 powder, 0.5 parts of water-soluble silicone oil, and 0.1 parts of dispersant, add them to a sand mill or a ball mill, and grind them to a slurry particle size of >2000 mesh to obtain slurry B; (3) Prepare a CaH4(C6H5O7)2 solution C with a pH of 4.5, mix slurry B with solution C in a ratio of 1:2, stir evenly, and concentrate at 50°C to a modified filler slurry with a solid content of 20%;

[0108] (b) Add the modified filler slurry into the stirrer according to the proportion, add the thickener, pH adjuster, dispersant, leveling agent and antioxidant, and stir at 2000r / min for 25min; then slowly add the ordinary filler, increase the stirring speed to 3500r / min, and stir for 25min;

[0109] (c) Finally, fluorocarbon emulsion was added, and then stirred at 1000 r / min for 10 min and allowed to stand, and vacuumed and defoamed to obtain an ultra-durable exterior wall coating.

[0110] Example 6

[0111] The difference from Example 1 is that Solution C is a CaH4(C6H5O7)2 solution C with a pH of 6.0, specifically, a super durable exterior wall coating, comprising, by weight:

[0112] 20 parts of fluorocarbon emulsion,

[0113] 25 parts of modified filler slurry with a solid content of 20%,

[0114] The film-forming agent is 12 parts of alcohol fat,

[0115] 2 parts of pH adjuster,

[0116] The common filler is 20 parts (5 parts limestone, 5 parts diatom mud, 5 parts mica powder and 5 parts talcum powder, the particle size of the common filler is 2000 mesh) and the dispersant is sodium lignin sulfonate, 0.3 parts,

[0117] The leveling agent is 1.0 part of carboxymethyl cellulose,

[0118] The thickener is 0.1 part of hydroxyethyl cellulose,

[0119] The antioxidant is 0.1 part of BHT antioxidant;

[0120] The preparation method is:

[0121] (a) Preparation of modified filler slurry: (1) Prepare a soluble silicate solution A with a mass fraction of 10%; (2) Take 20 parts of solution A, 5 parts of 400-mesh titanium dioxide, 0.2 parts of La2O3, 4 parts of 400-mesh Al2O3, 3 parts of 2000-mesh SiO2 powder, 0.5 parts of water-soluble silicone oil, and 0.1 parts of dispersant, add them to a sand mill or a ball mill, and grind them to a slurry particle size of >2000 mesh to obtain slurry B; (3) Prepare a CaH4(C6H5O7)2 solution C with a pH of 6.0, mix slurry B with solution C in a ratio of 1:1, stir evenly, and then concentrate at 50°C to a modified filler slurry with a solid content of 20%;

[0122] (b) Add the modified filler slurry into the stirrer according to the proportion, add the thickener, pH adjuster, dispersant, leveling agent and antioxidant, and stir at 2000r / min for 25min; then slowly add the ordinary filler, increase the stirring speed to 3500r / min, and stir for 25min;

[0123] (c) Finally, fluorocarbon emulsion was added, and then stirred at 1000 r / min for 10 min and allowed to stand, and vacuumed and defoamed to obtain an ultra-durable exterior wall coating.

[0124] Example 7

[0125] The difference from Example 1 is that slurry B is mixed with solution C in a ratio of 1:3. Specifically, a super durable exterior wall coating comprises, in parts by weight:

[0126] 20 parts of fluorocarbon emulsion,

[0127] 25 parts of modified filler slurry with a solid content of 20%,

[0128] The film-forming agent is 12 parts of alcohol fat,

[0129] 2 parts of pH adjuster,

[0130] The common filler is 20 parts (5 parts limestone, 5 parts diatom mud, 5 parts mica powder and 5 parts talcum powder, the particle size of the common filler is 2000 mesh) and the dispersant is sodium lignin sulfonate, 0.3 parts,

[0131] The leveling agent is 1.0 part of carboxymethyl cellulose,

[0132] The thickener is 0.1 part of hydroxyethyl cellulose,

[0133] The antioxidant is 0.1 part of BHT antioxidant;

[0134] The preparation method is:

[0135] (a) Preparation of modified filler slurry: (1) Prepare a soluble silicate solution A with a mass fraction of 10%; (2) Take 20 parts of solution A, 5 parts of 400-mesh titanium dioxide, 0.2 parts of La2O3, 4 parts of 400-mesh Al2O3, 3 parts of 2000-mesh SiO2 powder, 0.5 parts of water-soluble silicone oil, and 0.1 parts of dispersant, add them to a sand mill or a ball mill, and grind them to a slurry particle size of >2000 mesh to obtain slurry B; (3) Prepare a CaH4(C6H5O7)2 solution C with a pH of 4.5, mix slurry B with solution C in a ratio of 1:3, stir evenly, and concentrate at 50°C to a modified filler slurry with a solid content of 20%;

[0136] (b) Add the modified filler slurry into the stirrer according to the proportion, add the thickener, pH adjuster, dispersant, leveling agent and antioxidant, and stir at 2000r / min for 25min; then slowly add the ordinary filler, increase the stirring speed to 3500r / min, and stir for 25min;

[0137] (c) Finally, fluorocarbon emulsion was added, and then stirred at 1000 r / min for 10 min and allowed to stand, and vacuumed and defoamed to obtain an ultra-durable exterior wall coating.

[0138] Example 8

[0139] The difference from Example 1 is that the components are different. Specifically, a super durable exterior wall coating comprises, by parts by weight:

[0140] 25 parts of fluorocarbon emulsion,

[0141] 25 parts of modified filler slurry with a solid content of 20%,

[0142] The film-forming agent is 12 parts of alcohol fat,

[0143] 2.5 parts of pH adjuster,

[0144] Ordinary filler is 5 parts (0.5 parts limestone, 0.5 parts diatom mud, 0.5 parts mica powder and 0.5 parts talcum powder, ordinary filler particle size is 2000 mesh)

[0145] The dispersant is sodium lignin sulfonate, 0.5 parts,

[0146] The leveling agent is 1.5 parts of carboxymethyl cellulose,

[0147] The thickener is 0.3 parts of hydroxyethyl cellulose,

[0148] The antioxidant is 0.2 parts of BHT antioxidant;

[0149] The preparation method is:

[0150] (a) Preparation of modified filler slurry: (1) Prepare a soluble silicate solution A with a mass fraction of 10%; (2) Take 20 parts of solution A, 5 parts of 400-mesh titanium dioxide, 0.2 parts of La2O3, 4 parts of 400-mesh Al2O3, 3 parts of 2000-mesh SiO2 powder, 0.5 parts of water-soluble silicone oil, and 0.1 parts of dispersant, add them to a sand mill or a ball mill, and grind them to a slurry particle size of >2000 mesh to obtain slurry B; (3) Prepare a CaH4(C6H5O7)2 solution C with a pH of 4.5, mix slurry B with solution C in a ratio of 1:3, stir evenly, and concentrate at 50°C to a modified filler slurry with a solid content of 20%;

[0151] (b) Add the modified filler slurry into the stirrer according to the proportion, add the thickener, pH adjuster, dispersant, leveling agent and antioxidant, and stir at 2000r / min for 25min; then slowly add the ordinary filler, increase the stirring speed to 3500r / min, and stir for 25min;

[0152] (c) Finally, fluorocarbon emulsion was added, and then stirred at 1000 r / min for 10 min and allowed to stand, and vacuumed and defoamed to obtain an ultra-durable exterior wall coating.

[0153] Comparative Example 1

[0154] The difference from Example 1 is that 20 parts of deionized water are added with 5 parts of 400-mesh titanium dioxide, 0.2 parts of La2O3, 4 parts of 400-mesh Al2O3, 3 parts of 2000-mesh SiO2 powder, 0.5 parts of water-soluble silicone oil, and 0.1 parts of dispersant, and the mixture is finely ground in a sand mill or a ball mill until the slurry particle size is greater than 2000 mesh to obtain a filler slurry without undergoing a reaction treatment of solution A and solution B. Specifically, in parts by weight, the mixture comprises:

[0155] 20 parts of fluorocarbon emulsion,

[0156] 25 parts of filler slurry with a solid content of 20%,

[0157] The film-forming agent is 12 parts of alcohol fat,

[0158] 2 parts of pH adjuster,

[0159] The common filler is 20 parts (5 parts limestone, 5 parts diatom mud, 5 parts mica powder and 5 parts talcum powder, the particle size of the common filler is 2000 mesh) and the dispersant is sodium lignin sulfonate, 0.3 parts,

[0160] The leveling agent is 1.0 part of carboxymethyl cellulose,

[0161] The thickener is 0.1 part of hydroxyethyl cellulose,

[0162] The antioxidant is 0.1 part of BHT antioxidant;

[0163] The preparation method is:

[0164] (a) Preparation of filler slurry: 20 parts of deionized water, 5 parts of 400-mesh titanium dioxide, 0.2 parts of La2O3, 4 parts of 400-mesh Al2O3, 3 parts of 2000-mesh SiO2 powder, 0.5 parts of water-soluble silicone oil, and 0.1 parts of dispersant are added to a sand mill or a ball mill and finely ground to a slurry particle size of >2000 mesh to obtain a filler slurry;

[0165] (b) Add filler slurry into a stirrer, add thickener, dispersant, leveling agent, antioxidant, and stir at 2000 r / min for 25 min; then slowly add ordinary filler, increase the stirring speed to 3500 r / min, and stir for 25 min;

[0166] (c) Finally, fluorocarbon emulsion was added, and then stirred at 1000 r / min for 10 min and allowed to stand, and vacuumed and defoamed to obtain an ultra-durable exterior wall coating.

[0167] Comparative Example 2

[0168] The difference from Example 1 is that 10 parts of modified filler slurry with a solid content of 20% are added, specifically, in parts by weight, including:

[0169] 20 parts of fluorocarbon emulsion,

[0170] 10 parts of modified filler slurry with a solid content of 20%,

[0171] The film-forming agent is 12 parts of alcohol fat,

[0172] 2 parts of pH adjuster,

[0173] The common filler is 20 parts (5 parts limestone, 5 parts diatom mud, 5 parts mica powder and 5 parts talcum powder, the particle size of the common filler is 2000 mesh) and the dispersant is sodium lignin sulfonate, 0.3 parts,

[0174] The leveling agent is 1.0 part of carboxymethyl cellulose,

[0175] The thickener is 0.1 part of hydroxyethyl cellulose,

[0176] The antioxidant is 0.1 part of BHT antioxidant;

[0177] The preparation method is:

[0178] (a) Preparation of modified filler slurry: (1) Prepare a soluble silicate solution A with a mass fraction of 10%; (2) Take 20 parts of solution A, 5 parts of 400-mesh titanium dioxide, 0.2 parts of La2O3, 4 parts of 400-mesh Al2O3, 3 parts of 2000-mesh SiO2 powder, 0.5 parts of water-soluble silicone oil, and 0.1 parts of dispersant, add them to a sand mill or a ball mill, and grind them to a slurry particle size of >2000 mesh to obtain slurry B; (3) Prepare a CaH4(C6H5O7)2 solution C with a pH of 4.5, mix slurry B with solution C in a ratio of 1:1, stir evenly, and then concentrate at 50°C to a modified filler slurry with a solid content of 20%;

[0179] (b) Add the modified filler slurry into the stirrer according to the proportion, add the thickener, pH adjuster, dispersant, leveling agent and antioxidant, and stir at 2000r / min for 25min; then slowly add the ordinary filler, increase the stirring speed to 3500r / min, and stir for 25min;

[0180] (c) Finally, fluorocarbon emulsion was added, and then stirred at 1000 r / min for 10 min and allowed to stand, and vacuumed and defoamed to obtain an ultra-durable exterior wall coating.

[0181] Comparative Example 3

[0182] The difference from Example 1 is that the solid content of the modified filler slurry is 15%;

[0183] In parts by weight, it includes:

[0184] 20 parts of fluorocarbon emulsion,

[0185] 25 parts of modified filler slurry with a solid content of 15%,

[0186] The film-forming agent is 12 parts of alcohol fat,

[0187] 2 parts of pH adjuster,

[0188] The common filler is 20 parts (5 parts limestone, 5 parts diatom mud, 5 parts mica powder and 5 parts talcum powder, the particle size of the common filler is 2000 mesh) and the dispersant is sodium lignin sulfonate, 0.3 parts,

[0189] The leveling agent is 1.0 part of carboxymethyl cellulose,

[0190] The thickener is 0.1 part of hydroxyethyl cellulose,

[0191] The antioxidant is 0.1 part of BHT antioxidant;

[0192] The preparation method is:

[0193] (a) Preparation of modified filler slurry: (1) Prepare a soluble silicate solution A with a mass fraction of 10%; (2) Take 20 parts of solution A, 5 parts of 400-mesh titanium dioxide, 0.2 parts of La2O3, 4 parts of 400-mesh Al2O3, 3 parts of 2000-mesh SiO2 powder, 0.5 parts of water-soluble silicone oil, and 0.1 parts of dispersant, add them to a sand mill or a ball mill, and grind them to a slurry particle size of >2000 mesh to obtain slurry B; (3) Prepare a CaH4(C6H5O7)2 solution C with a pH of 4.5, mix slurry B with solution C in a ratio of 1:1, stir evenly, and then concentrate at 50°C to a modified filler slurry with a solid content of 15%;

[0194] (b) Add the modified filler slurry into the stirrer according to the proportion, add the thickener, pH adjuster, dispersant, leveling agent and antioxidant, and stir at 2000r / min for 25min; then slowly add the ordinary filler, increase the stirring speed to 3500r / min, and stir for 25min;

[0195] (c) Finally, fluorocarbon emulsion was added, and then stirred at 1000 r / min for 10 min and allowed to stand, and vacuumed and defoamed to obtain an ultra-durable exterior wall coating.

[0196] Comparative Example 4

[0197] The difference from Example 1 is that the solid content of the modified filler slurry is 35%, specifically, in parts by weight, comprising:

[0198] 20 parts of fluorocarbon emulsion,

[0199] 25 parts of modified filler slurry with a solid content of 35%,

[0200] The film-forming agent is 12 parts of alcohol fat,

[0201] 2 parts of pH adjuster,

[0202] The common filler is 20 parts (5 parts limestone, 5 parts diatom mud, 5 parts mica powder and 5 parts talcum powder, the particle size of the common filler is 2000 mesh) and the dispersant is sodium lignin sulfonate, 0.3 parts,

[0203] The leveling agent is 1.0 part of carboxymethyl cellulose,

[0204] The thickener is 0.1 part of hydroxyethyl cellulose,

[0205] The antioxidant is 0.1 part of BHT antioxidant;

[0206] The preparation method is:

[0207] (a) Preparation of modified filler slurry: (1) Prepare a soluble silicate solution A with a mass fraction of 10%; (2) Take 20 parts of solution A, 5 parts of 400-mesh titanium dioxide, 0.2 parts of La2O3, 4 parts of 400-mesh Al2O3, 3 parts of 2000-mesh SiO2 powder, 0.5 parts of water-soluble silicone oil, and 0.1 parts of dispersant, add them to a sand mill or a ball mill, and grind them to a slurry particle size of >2000 mesh to obtain slurry B; (3) Prepare a CaH4(C6H5O7)2 solution C with a pH of 4.5, mix slurry B with solution C in a ratio of 1:1, stir evenly, and then concentrate at 50°C to a modified filler slurry with a solid content of 35%;

[0208] (b) Add the modified filler slurry into the stirrer according to the proportion, add the thickener, pH adjuster, dispersant, leveling agent and antioxidant, and stir at 2000r / min for 25min; then slowly add the ordinary filler, increase the stirring speed to 3500r / min, and stir for 25min;

[0209] (c) Finally, fluorocarbon emulsion was added, and then stirred at 1000 r / min for 10 min and allowed to stand, and vacuumed and defoamed to obtain an ultra-durable exterior wall coating.

[0210] Comparative Example 5

[0211] The difference from Example 1 is that a CaH4(C6H5O7)2 solution C with a pH of 7 is prepared, specifically, in parts by weight, comprising:

[0212] 20 parts of fluorocarbon emulsion,

[0213] 25 parts of modified filler slurry with a solid content of 20%,

[0214] The film-forming agent is 12 parts of alcohol fat,

[0215] 2 parts of pH adjuster,

[0216] The common filler is 20 parts (5 parts limestone, 5 parts diatom mud, 5 parts mica powder and 5 parts talcum powder, the particle size of the common filler is 2000 mesh) and the dispersant is sodium lignin sulfonate, 0.3 parts,

[0217] The leveling agent is 1.0 part of carboxymethyl cellulose,

[0218] The thickener is 0.1 part of hydroxyethyl cellulose,

[0219] The antioxidant is 0.1 part of BHT antioxidant;

[0220] The preparation method is:

[0221] (a) Preparation of modified filler slurry: (1) Prepare a soluble silicate solution A with a mass fraction of 10%; (2) Take 20 parts of solution A, 5 parts of 400-mesh titanium dioxide, 0.2 parts of La2O3, 4 parts of 400-mesh Al2O3, 3 parts of 2000-mesh SiO2 powder, 0.5 parts of water-soluble silicone oil, and 0.1 parts of dispersant, add them to a sand mill or a ball mill, and grind them to a slurry particle size of >2000 mesh to obtain slurry B; (3) Prepare a CaH4(C6H5O7)2 solution C with a pH of 7, mix slurry B with solution C in a ratio of 1:1, stir evenly, and then concentrate at 50°C to a modified filler slurry with a solid content of 20%;

[0222] (b) Add the modified filler slurry into the stirrer according to the proportion, add the thickener, pH adjuster, dispersant, leveling agent and antioxidant, and stir at 2000r / min for 25min; then slowly add the ordinary filler, increase the stirring speed to 3500r / min, and stir for 25min;

[0223] (c) Finally, fluorocarbon emulsion was added, and then stirred at 1000 r / min for 10 min and allowed to stand, and vacuumed and defoamed to obtain an ultra-durable exterior wall coating.

[0224] Comparative Example 6

[0225] The difference from Example 1 is that a CaH4(C6H5O7)2 solution C with a pH of 4.0 is prepared, specifically, in parts by weight, comprising:

[0226] 20 parts of fluorocarbon emulsion,

[0227] 25 parts of modified filler slurry with a solid content of 20%,

[0228] The film-forming agent is 12 parts of alcohol fat,

[0229] 2 parts of pH adjuster,

[0230] The common filler is 20 parts (5 parts limestone, 5 parts diatom mud, 5 parts mica powder and 5 parts talcum powder, the particle size of the common filler is 2000 mesh) and the dispersant is sodium lignin sulfonate, 0.3 parts,

[0231] The leveling agent is 1.0 part of carboxymethyl cellulose,

[0232] The thickener is 0.1 part of hydroxyethyl cellulose,

[0233] The antioxidant is 0.1 part of BHT antioxidant;

[0234] The preparation method is:

[0235] (a) Preparation of modified filler slurry: (1) Prepare a soluble silicate solution A with a mass fraction of 10%; (2) Take 20 parts of solution A, 5 parts of 400-mesh titanium dioxide, 0.2 parts of La2O3, 4 parts of 400-mesh Al2O3, 3 parts of 2000-mesh SiO2 powder, 0.5 parts of water-soluble silicone oil, and 0.1 parts of dispersant, add them to a sand mill or a ball mill, and grind them to a slurry particle size of >2000 mesh to obtain slurry B; (3) Prepare a CaH4(C6H5O7)2 solution C with a pH of 4.0, mix slurry B with solution C in a ratio of 1:1, stir evenly, and concentrate at 50°C to a modified filler slurry with a solid content of 20%;

[0236] (b) Add the modified filler slurry into the stirrer according to the proportion, add the thickener, pH adjuster, dispersant, leveling agent and antioxidant, and stir at 2000r / min for 25min; then slowly add the ordinary filler, increase the stirring speed to 3500r / min, and stir for 25min;

[0237] (c) Finally, fluorocarbon emulsion was added, and then stirred at 1000 r / min for 10 min and allowed to stand, and vacuumed and defoamed to obtain an ultra-durable exterior wall coating.

[0238] Comparative Example 7

[0239] The difference from Example 1 is that no lanthanum oxide is added to the modified filler slurry. Specifically, in parts by weight, the modified filler slurry comprises:

[0240] 20 parts of fluorocarbon emulsion,

[0241] 25 parts of modified filler slurry with a solid content of 20%,

[0242] The film-forming agent is 12 parts of alcohol fat,

[0243] 2 parts of pH adjuster,

[0244] The common filler is 20 parts (5 parts limestone, 5 parts diatom mud, 5 parts mica powder and 5 parts talcum powder, the particle size of the common filler is 2000 mesh) and the dispersant is sodium lignin sulfonate, 0.3 parts,

[0245] The leveling agent is 1.0 part of carboxymethyl cellulose,

[0246] The thickener is 0.1 part of hydroxyethyl cellulose,

[0247] The antioxidant is 0.1 part of BHT antioxidant;

[0248] The preparation method is:

[0249] (a) Preparation of modified filler slurry: (1) Prepare a soluble silicate solution A with a mass fraction of 10%; (2) Take 20 parts of solution A, 5 parts of 400-mesh titanium dioxide, 4 parts of 400-mesh Al2O3, 3 parts of 2000-mesh SiO2 powder, 0.5 parts of water-soluble silicone oil, and 0.1 parts of dispersant, add them to a sand mill or a ball mill, and grind them to a slurry particle size of >2000 mesh to obtain slurry B; (3) Prepare a CaH4(C6H5O7)2 solution C with a pH of 4.5, mix slurry B with solution C in a ratio of 1:1, stir evenly, and then concentrate at 50°C to a modified filler slurry with a solid content of 20%;

[0250] (b) Add the modified filler slurry into the stirrer according to the proportion, add the thickener, pH adjuster, dispersant, leveling agent and antioxidant, and stir at 2000r / min for 25min; then slowly add the ordinary filler, increase the stirring speed to 3500r / min, and stir for 25min;

[0251] (c) Finally, fluorocarbon emulsion was added, and then stirred at 1000 r / min for 10 min and allowed to stand, and vacuumed and defoamed to obtain an ultra-durable exterior wall coating.

[0252] Comparative Example 8

[0253] The difference from Example 1 is that the modified filler slurry does not contain water-soluble silicone oil. Specifically, in parts by weight, it includes:

[0254] 20 parts of fluorocarbon emulsion,

[0255] 25 parts of modified filler slurry with a solid content of 20%,

[0256] The film-forming agent is 12 parts of alcohol fat,

[0257] 2 parts of pH adjuster,

[0258] The common filler is 20 parts (5 parts limestone, 5 parts diatom mud, 5 parts mica powder and 5 parts talcum powder, the particle size of the common filler is 2000 mesh) and the dispersant is sodium lignin sulfonate, 0.3 parts,

[0259] The leveling agent is 1.0 part of carboxymethyl cellulose,

[0260] The thickener is 0.1 part of hydroxyethyl cellulose,

[0261] The antioxidant is 0.1 part of BHT antioxidant;

[0262] The preparation method is:

[0263] (a) Preparation of modified filler slurry: (1) Prepare a soluble silicate solution A with a mass fraction of 10%; (2) Take 20 parts of solution A, 5 parts of 400-mesh titanium dioxide, 0.2 parts of La2O3, 4 parts of 400-mesh Al2O3, 3 parts of 2000-mesh SiO2 powder, and 0.1 parts of dispersant, add them to a sand mill or a ball mill, and grind them to a slurry particle size of >2000 mesh to obtain slurry B; (3) Prepare a CaH4(C6H5O7)2 solution C with a pH of 4.5, mix slurry B with solution C in a ratio of 1:1, stir evenly, and then concentrate at 50°C to a modified filler slurry with a solid content of 20%;

[0264] (b) Add the modified filler slurry into the stirrer according to the proportion, add the thickener, pH adjuster, dispersant, leveling agent and antioxidant, and stir at 2000r / min for 25min; then slowly add the ordinary filler, increase the stirring speed to 3500r / min, and stir for 25min;

[0265] (c) Finally, fluorocarbon emulsion was added, and then stirred at 1000 r / min for 10 min and allowed to stand, and vacuumed and defoamed to obtain an ultra-durable exterior wall coating.

[0266] Comparative Example 9

[0267] The difference from Example 1 is that a Na2H4(C6H5O7)2 solution C with a pH of 4.5 is prepared, specifically, in parts by weight, comprising:

[0268] 20 parts of fluorocarbon emulsion,

[0269] 25 parts of modified filler slurry with a solid content of 20%,

[0270] The film-forming agent is 12 parts of alcohol fat,

[0271] 2 parts of pH adjuster,

[0272] The common filler is 20 parts (5 parts limestone, 5 parts diatom mud, 5 parts mica powder and 5 parts talcum powder, the particle size of the common filler is 2000 mesh) and the dispersant is sodium lignin sulfonate, 0.3 parts,

[0273] The leveling agent is 1.0 part of carboxymethyl cellulose,

[0274] The thickener is 0.1 part of hydroxyethyl cellulose,

[0275] The antioxidant is 0.1 part of BHT antioxidant;

[0276] The preparation method is:

[0277] (a) Preparation of modified filler slurry: (1) Prepare a soluble silicate solution A with a mass fraction of 10%; (2) Take 20 parts of solution A, 5 parts of 400-mesh titanium dioxide, 0.2 parts of La2O3, 4 parts of 400-mesh Al2O3, 3 parts of 2000-mesh SiO2 powder, 0.5 parts of water-soluble silicone oil, and 0.1 parts of dispersant, add them to a sand mill or a ball mill, and grind them to a slurry particle size of >2000 mesh to obtain slurry B; (3) Prepare a Na2H4(C6H5O7)2 solution C with a pH of 4.5, mix slurry B with solution C in a ratio of 1:1, stir evenly, and concentrate at 50°C to a modified filler slurry with a solid content of 20%;

[0278] (b) Add the modified filler slurry into the stirrer according to the proportion, add the thickener, pH adjuster, dispersant, leveling agent and antioxidant, and stir at 2000r / min for 25min; then slowly add the ordinary filler, increase the stirring speed to 3500r / min, and stir for 25min;

[0279] (c) Finally, fluorocarbon emulsion was added, and then stirred at 1000 r / min for 10 min and allowed to stand, and vacuumed and defoamed to obtain an ultra-durable exterior wall coating.

[0280] Comparative Example 10

[0281] The difference from Example 1 is that a Ca(CH3COO)2 solution C with a pH of 4.5 is prepared, specifically, in parts by weight, comprising:

[0282] 20 parts of fluorocarbon emulsion,

[0283] 25 parts of modified filler slurry with a solid content of 20%,

[0284] The film-forming agent is 12 parts of alcohol fat,

[0285] 2 parts of pH adjuster,

[0286] The common filler is 20 parts (5 parts limestone, 5 parts diatom mud, 5 parts mica powder and 5 parts talcum powder, the particle size of the common filler is 2000 mesh) and the dispersant is sodium lignin sulfonate, 0.3 parts,

[0287] The leveling agent is 1.0 part of carboxymethyl cellulose,

[0288] The thickener is 0.1 part of hydroxyethyl cellulose,

[0289] The antioxidant is 0.1 part of BHT antioxidant;

[0290] The preparation method is:

[0291] (a) Preparation of modified filler slurry: (1) Prepare a soluble silicate solution A with a mass fraction of 10%; (2) Take 20 parts of solution A, 5 parts of 400-mesh titanium dioxide, 0.2 parts of La2O3, 4 parts of 400-mesh Al2O3, 3 parts of 2000-mesh SiO2 powder, 0.5 parts of water-soluble silicone oil, and 0.1 parts of dispersant, add them to a sand mill or a ball mill, and grind them to a slurry particle size of >2000 mesh to obtain slurry B; (3) Prepare a Ca(CH3COO)2 solution C with a pH of 4.5, mix slurry B with solution C in a ratio of 1:1, stir evenly, and concentrate at 50°C to a modified filler slurry with a solid content of 20%;

[0292] (b) Add the modified filler slurry into the stirrer according to the proportion, add the thickener, pH adjuster, dispersant, leveling agent and antioxidant, and stir at 2000r / min for 25min; then slowly add the ordinary filler, increase the stirring speed to 3500r / min, and stir for 25min;

[0293] (c) Finally, fluorocarbon emulsion was added, and then stirred at 1000 r / min for 10 min and allowed to stand, and vacuumed and defoamed to obtain an ultra-durable exterior wall coating.

[0294] Performance Test:

[0295] The super durable exterior wall coatings obtained in Examples 1-8 and Comparative Examples 1-10 were tested for the following performance indicators:

[0296] 1. Test heat storage stability, low temperature storage stability and contrast ratio according to JG / T 26~2002;

[0297] 2. Test the drying time according to Method B in GB / T 1728~1979 (1989) "Determination of Drying Time of Paint Film and Putty Film";

[0298] 3. Test the scrub resistance according to GB 9266~2009 "Determination of scrub resistance of architectural coatings";

[0299] 4. Test water resistance according to Method A of GB / T 1733~1993 "Determination of water resistance of paint film";

[0300] 5. Test alkali resistance according to GB / T 9265~2009 "Determination of alkali resistance of architectural coatings";

[0301] 6. Test the temperature change resistance according to JG / T 25~1999 "Determination of freeze-thaw cycle resistance of architectural coatings":

[0302] 7. Test the artificial aging resistance (anti-oxidation and anti-ultraviolet effect) according to GB / T 1865~2009 "Artificial weathering and artificial radiation exposure of paints and varnishes to filtered xenon arc radiation":

[0303] 8. Test the coating adhesion according to the coating adhesion test specification and standard: 1. First cut 6 or 11 parallel cuts with equal spacing (can be divided into 1mm or 2mm) on the test piece coating, and then cut vertically with the same number and spacing as the previous cuts. When the coating thickness is less than or equal to 60um, use a cutter with a cutter blade spacing of 1mm. When the coating thickness is greater than 60um, use a cutter with a cutter blade spacing of 2mm. 2. When cutting manually, the force should be uniform and the speed should be steady without shaking, so that the blade can just penetrate the coating and touch the substrate during cutting. Excessive or uneven force may affect the test results. 3. After cutting, 25 or 100 squares will appear on the test plate. Use a soft brush to gently brush off the chips along the two diagonal directions of the squares, and then check and evaluate the coating adhesion. The evaluation standard for the cross-cut method test of coating adhesion refers to GB / T9286-88 (0-5 levels, 0 level has the best adhesion effect).

[0304] The test results are shown in Table 1.

[0305] Table 1

[0306] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Comparative Example 9 Comparative Example 10 Construction Paint two layers of barrier-free Paint two layers of barrier-free Paint two layers of barrier-free Paint two layers of barrier-free Paint two layers of barrier-free Paint two layers of barrier-free Paint two layers of barrier-free Paint two layers of barrier-free Paint two layers of barrier-free Paint two layers of barrier-free Paint two layers of barrier-free Paint two layers of barrier-free Paint two layers of barrier-free Paint two layers of barrier-free Paint two layers of barrier-free Paint two layers of barrier-free Paint two layers of barrier-free Paint two layers of barrier-free Coating appearance normal normal normal normal normal normal normal normal Concave and convex normal normal normal normal normal normal Concave and convex normal normal Contrast ratio (white) 0.97 0.98 0.97 0.96 0.97 0.98 0.96 0.96 0.98 0.97 0.98 0.96 0.96 0.95 0.96 0.97 0.96 0.93 Thermal storage stability (30 days) No caking, condensation or mildew No caking, condensation or mildew No caking, condensation or mildew No caking, condensation or mildew No caking, condensation or mildew No caking, condensation or mildew No caking, condensation or mildew No caking, condensation or mildew No caking, condensation or mildew No caking, condensation or mildew No caking, condensation or mildew No caking, condensation or mildew No caking, condensation or mildew Cohesion No caking, condensation or mildew Cohesion Cohesion No caking, condensation or mildew Low temperature storage stability (3 times) No caking, no agglomeration No caking, no agglomeration No caking, no agglomeration No caking, no agglomeration No caking, condensation or mildew No caking, condensation or mildew No caking, condensation or mildew No caking, condensation or mildew Cohesion No caking, condensation or mildew Cohesion No caking, condensation or mildew No caking, condensation or mildew No caking, condensation or mildew No caking, condensation or mildew Cohesion No caking, no aggregation Cohesion Surface drying time (h) 0.4 0.5 0.7 0.5 0.4 0.6 0.7 0.6 1.5 0.3 0.9 1.0 1.3 1.4 1.5 1.0 1.3 1.2 Washability / times 19903 19849 19647 19032 19356 19125 19524 19584 10322 15635 16452 11028 10077 10586 10348 12101 9684 9640 Water resistance (168h) No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering Severe peeling and powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering Cracks, peeling No blistering, cracking, peeling or powdering Loss of fans crack Peeling and powdering Alkali resistance (168h) No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering crack Flaking No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering Loss of fans Flaking Cracks, peeling Peeling and powdering Cracks, peeling, powdering Powder loss is serious Temperature resistance (10 times) No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering Loss of fans No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering No blistering, cracking, peeling or powdering Flaking No blistering, cracking, peeling or powdering Cracks, peeling Cracks, powder loss There is foaming There is foaming Stain resistance (%) 7 9 6 9 9 8 9 6 16 18 11 15 14 15 18 25 28 15 Artificial aging resistance (white, Ⅱ500h) No blistering, cracking, peeling, powdering level 0, discoloration level 0 No blistering, cracking, peeling, powdering level 0, discoloration level 0 No blistering, cracking, peeling, powdering level 0, discoloration level 0 No blistering, cracking, peeling, powdering level 0, discoloration level 0 No blistering, cracking, peeling, powdering level 0, discoloration level 0 No blistering, cracking, peeling, powdering level 0, discoloration level 0 No blistering, cracking, peeling, powdering level 0, discoloration level 0 No blistering, cracking, peeling, powdering level 0, discoloration level 0 No blistering, cracking, peeling, chalking level 3, discoloration level 3 Foaming and powdering: 1 level, discoloration: 0 level No blistering, cracking, peeling, chalking level 0, discoloration level 1 No blistering, cracking, peeling, chalking level 0, discoloration level 1 Powdering level 2, color change level 2 No blistering, cracking, peeling, chalking level 0, discoloration level 2 No blistering, cracking, peeling, chalking level 1, discoloration level 4 No blistering, cracking, peeling, chalking level 1, discoloration level 3 Blistering, cracking, peeling, chalking level 0, discoloration level 3 Blistering, cracking, peeling, chalking 4 levels, discoloration 2 levels Adhesion test Level 0 Level 0 Level 1 Level 0 Level 0 Level 0 Level 0 Level 0 Level 3 Level 3 Level 2 Level 3 Level 4 Level 3 Level 3 Level 3 Level 4 Level 3

[0307] From the data in Table 1, it can be seen that Examples 1-8 of the present invention have good performance in terms of scrub resistance, alkali resistance, temperature change resistance, artificial aging resistance and adhesion test, while Comparative Examples 1-10 have insufficient adhesion test. At the same time, Comparative Examples 1, 6, 8-10 also have insufficient water resistance, alkali resistance, temperature change resistance, etc.; Comparative Example 2, Comparative Example 5, Comparative Example 7 have insufficient alkali resistance; Comparative Example 3 and Comparative Example 4 also have problems such as poor scrub resistance. This shows that the ultra-durable exterior wall coating prepared by the present invention has advantages in durability, and the modified filler slurry of the present invention has the effect of improving the durability of the exterior wall coating. It also shows that the modified filler slurry of the present invention can not only enhance the durability of the coating, but also meet the standard requirements in terms of construction performance.

[0308] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A super durable exterior wall paint, characterized in that: In parts by weight, it includes: 20~30 parts of fluorocarbon emulsion, 20~25 parts of modified filler slurry with a solid content of 20%~30%, The film-forming agent is 2~3 parts, 2~3 parts of pH adjuster, Ordinary fillers are 20~40 parts, Dispersant is 0.3~0.9 parts, Leveling agent is 1.0~1.6 parts, Thickener is 0.1~0.5 parts, Antioxidant: 0.1~0.2 parts; The modified filler slurry is prepared by the following method: (1) Prepare a soluble silicate solution A with a mass fraction of 8-15%; (2) Take 10-20 parts of solution A, 4-10 parts of titanium dioxide with a mesh size of 400 or more, 0.1-0.3 parts of La2O3, 3-5 parts of Al2O3 with a mesh size of 400 or more, 20-40 parts of SiO2 powder with a mesh size of 2000 or more, 0.4-1 parts of water-soluble silicone oil, and 0.1-0.3 parts of dispersant, add them to a sand mill or a ball mill, and grind them into a slurry particle size of >2000 mesh to obtain slurry B; (3) Prepare Ca2+ with pH of 4.5-6.5 x (H) 6-2x (C6H5O7)2 solution C, slurry B is mixed with solution C in a ratio of 1:1-1:3 and stirred evenly, and then concentrated into a modified filler slurry with a solid content of 20%~30%, 0.5<x<2.

5.

2. The ultra-durable exterior wall paint according to claim 1, characterized in that: The solute of the soluble silicate solution A in step (1) is sodium silicate or potassium silicate, and the modulus is 2-5.

3. The ultra-durable exterior wall paint according to claim 1, characterized in that: In step (3), the slurry B and solution C are mixed and stirred in a ratio of 1:1-1:3, and then concentrated at 50-70° C. to a modified filler slurry with a solid content of 20%-30%.

4. The ultra-durable exterior wall paint according to claim 1, characterized in that: The water-soluble silicone oil in step (2) is a polysiloxane-polyalkoxy ether copolymer.

5. The ultra-durable exterior wall paint according to claim 1, characterized in that: The film-forming agent is alcohol lipid twelve.

6. The ultra-durable exterior wall paint according to claim 1, characterized in that: The common filler includes at least three of limestone, diatom mud, mica powder and talcum powder, and the particle size of the common filler is greater than 1500 meshes.

7. The ultra-durable exterior wall paint according to claim 1, characterized in that: The dispersant is sodium lignin sulfonate or sodium humate.

8. The ultra-durable exterior wall paint according to claim 1, characterized in that: The leveling agent is carboxymethyl cellulose; the thickener is hydroxyethyl cellulose; and the antioxidant is BHT antioxidant.

9. A method for preparing the ultra-durable exterior wall coating according to any one of claims 1 to 8, characterized in that: The preparation steps are: (a) preparing a modified filler slurry; (b) Add the modified filler slurry into the stirrer according to the formula ratio, add the thickener, pH adjuster, dispersant, leveling agent, antioxidant and film-forming agent, and stir at 2000-3000 r / min for 20-30 min; then slowly add the ordinary filler, increase the stirring speed to 3500-4500 r / min, and stir for 20-30 min; (c) Finally, add fluorocarbon emulsion, then stir at 500-1000 r / min for 5-15 min and let stand, and vacuum and defoam to obtain ultra-durable exterior wall coating.

Citation Information

Patent Citations

  • Durable exterior wall coating

    CN104804577A

  • High-durability exterior wall coating and preparation method thereof

    CN115558397A

  • Composite elastic anti-crack water-based exterior wall coating material and preparation method thereof

    CN104277524A

  • Durable exterior wall latex paint for buildings, and preparation method thereof

    CN109971263A